The marketisation of rehabilitation: some economic considerations - Albertson, Kevin (Probation journal, 2019)
This paper considers criminal justice policy in England and Wales since the Transforming Rehabilitation (TR) agenda implemented in 2013. TR rested on the proposition that probation services are best provided in a market context. Motivated by profit and extrinsic rewards, private sector consortia, and their employees, theoretically act efficiently to deter and rehabilitate offenders from crime. However, there is evidence that marketisation itself undermines the prospects of efficient social policy. Over-reliance on markets may undermine pro-social norms through emphasising individualism and extrinsic returns. Outsourcing is also associated with increasing inequality, which may also undermine pro-social norms. Further, the emphasis placed on self-interest in framing market-based incentive structures is associated with declining public welfare support for the economically marginalised and increased use of relatively expensive incarceration. In application, TR proved unsustainable. The innovation involves increasing reliance on the para-state sector, in which private profits rely on public payment. However, the profits expected under TR fell short of expectations, in part due to changes in wider society. The early cancellation of TR contracts highlights the inflexible nature of such public sector procurement. On the basis of theory and practice, we suggest a reconsideration of the government’s position on probation and set out reasonable steps to address shortcomings in the current system.